A 34-week-old male fetus with short rib polydactyly syndrome (SRPS) type I (Saldino-Noonan) with pancreatic cysts - Balci, Sevim; Altinok, Gülçin; Tekşen, Fulya; Eryilmaz, Muzaffer (The Turkish Journal of Pediatrics, 2003)
A 34-week-old male fetus (first diagnosed at 28 weeks of gestation) with short rib polydactyly type I Saldino-Noonan syndrome is presented in this study. In the postmortem examination of the fetus, pancreatic dysplasia, multiple cysts and multicystic dysplastic kidneys, omphalomesenteric cyst, ascites, malrotation, micropenis, undescended testes, bilateral inguinal hernia and hydrops were observed. The parents were first-degree cousins. One male and one female sibling had similar findings and both had died after birth. Only a four-year-old healthy daughter was alive. We believe these findings will be helpful in the differential diagnosis of further lethal skeletal dysplasia cases.